2021
DOI: 10.1097/bot.0000000000002189
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Triceps Avulsion Fracture After Proximal Ulna Plate Fixation

Abstract: Objectives: Triceps avulsion fractures have become an increasingly common postoperative complication of olecranon fracture repair with proximal ulna plate (PUP) fixation. The purpose of this study is to create an efficient, reproducible mechanism to mitigate this issue.Methods: Ten matched pair cadaveric specimens underwent a complete transverse osteotomy to simulate an olecranon fracture, followed by fracture reduction with a PUP. One arm from each pair underwent an additional augmented suture repair, where t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Orbay et al ( 13 ) proposed an augmented suture of the triceps tendon directly to the plate. They found that olecranon avulsion fracture became a postoperative complication after plate fixation of an olecranon fracture, which inspired their solution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orbay et al ( 13 ) proposed an augmented suture of the triceps tendon directly to the plate. They found that olecranon avulsion fracture became a postoperative complication after plate fixation of an olecranon fracture, which inspired their solution.…”
Section: Discussionmentioning
confidence: 99%
“…Considering these postoperative side effects and complications of TBW, plates are recommended for the fixation of olecranon avulsion fractures. However, for this fracture type, only one screw should be used to fix the small proximal fracture fragment ( 13 ). The fixation is considered to provide insufficient stability, and early postoperative functional exercise may lead to fixation failure.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that the most common mode of failure was the loss of fixation of the proximal olecranon fragment. Orbay et al conducted a similar biomechanical study of 10 paired cadaveric specimens, in which 1 arm from each pair underwent an additional augmented suture repair after plate fixation of a transverse olecranon osteotomy where the triceps tendon was sutured directly to the plate 5 . With suture augmentation, 4 elbows failed through triceps rupture.…”
Section: Discussionmentioning
confidence: 99%
“…Risk of failure may have been increased by iatrogenic damage to the tendon when split for plate placement or through increased load placed on the tendon with suture augmentation. Although theoretically suture augmentation should be protective of the triceps insertion, the data from Orbay et al suggest that suturing the triceps to the plate, while protective of the fracture, may actually increase the risk of tendon rupture 5 . A limitation of our case report is the possibility that the triceps ruptured independently because of the mechanism of the injury, and therefore, the longitudinal split and suture augmentation may not have contributed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation